Odpowiedzi

Najlepsza Odpowiedź!
2010-01-14T00:07:03+01:00
A = (-2; 4)
x² + y² - 6x + 4y + c = 0
a)
(-2)² + 4² - 6*(-2) + 4*4 + c = 0
4 + 16 + 12 + 16 + c = 0
48 + c = 0
c = - 48
Równanie okręgu jest zatem nastepujace
x² + y² - 6x + 4y - 48 = 0
(x -3)² -9 + (y +2)² - 4 - 48 = 0
(x - 3)² + (y + 2)² = 61
r = √61
b)
Równania 4 stycznych do tego okręgu ( równoległych do osi OY
oraz do osi OX ):

x = 3 - r = 3 - √61
x = 3 + r = 3 + √61
y = -2 - r = -2 - √61
y = -2 + r = -2 + √61

Odp. x = 3 - √61
x = 3 + √61
y = -2 - √61
y = -2 + √61
3 2 3